Randomized comparison of high-frequency ventilation with high-rate intermittent positive pressure ventilation in preterm infants with respiratory failure - Thome, Ulrich; Kössel, Hans; Lipowsky, Gert; Porz, Friedrich; Fürste, Hans-Otto; Genzel-Boroviczeny, Orsolya; Tröger, Jochen; Oppermann, Hans-Conrad; Högel, Josef; Pohlandt, Frank (The journal of pediatrics, 1999)
In a randomized, controlled, multicenter trial, we tested the hypothesis that high-frequency ventilation (HFV) with a high lung volume strategy results in fewer treatment failures than intermittent positive pressure ventilation (IPPV) with high rates and low peak inspiratory pressures.
Elektronische Reproduktion der Druck-Ausgabe
Available online 4 November 2005
Available online 4 November 2005
Gesehen am 13.01.2021